Right to Education as a Fundamental Right: A Review on Sri Lankan Perspective - Amarasinghe, Kusal (Law Students' Human Rights Movement, Sri Lanka Law College, 2023)
Education is nothing but an instrument to explore new knowledge for the progress of human civilization. Accordingly, education is the socially organized and regulated process of continuous transference of socially significant experiences from previous to following generations (Naziev,2017). Education is a process that begins at birth and continues until the end of life, (Arslan,2018) hence it is said that ‘learning’ is a lifelong journey. The role of education in creating, preserving and sustaining the right knowledge, skills and attitudes in the context of the social value system are crucial for the wellbeing of any civilized society. (Alawattegama,2020). Thus, education should be identified as a fundamental factor which essential for every human being to achieve social, economic, cultural and political well-being. Sri Lanka is the only country in the entire South Asian region where the government provides free education from primary to university. The Free Education system in Sri Lanka plays a very significant role in achieving sustainable development and strengthening social, cultural, historical and integral development, and is often called the backbone of the society. Free Education is not only to provide ‘education’ free of cost but to provide equitable access to education to every child irrespective of any social, economic and cultural ground. Although, education has not been recognized as a fundamental right by the constitution, providing education for the citizens has been recognized as a state obligation in Sri Lanka.
Keywords: Free Education; Right to Education; Sri Lanka